Question
upstudy study bank question image url

Prove that: \( \frac{1}{\tan } a(\sin a \tan a+\cos a)=\frac{1}{\sin a} \) If \( (4 \theta-8) \sin 30^{\circ}=\left(\theta^{3}-8\right) \) and \( \left(Q^{2}+2 \theta+4\right)=2 \), determine value ofs \( \tan 240^{\circ} \), withoud the use of a calculator Determine the general Solution of: a) \( 2 \cos 2 \theta=-0,44 \) b) \( 2 \cos ^{2} \theta-\cos Q=0 \)

Ask by Bowen Medina. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

- **Proven Equation:** \( \frac{1}{\tan a}(\sin a \tan a + \cos a) = \frac{1}{\sin a} \) - **Solutions for \( \theta \):** \( \theta = 2, -1 + i, -1 - i \) - **Value of \( \tan 240^{\circ} \):** \( \sqrt{3} \) - **General Solutions:** - \( 2 \cos 2\theta = -0.44 \): \( \theta = \frac{\pm \cos^{-1}(-0.22) + 2n\pi}{2} \) - \( 2 \cos^{2} \theta - \cos Q = 0 \): \( Q = \pm \cos^{-1}(2 \cos^{2} \theta) + 2m\pi \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Mind Expander

To prove that \( \frac{1}{\tan a} (\sin a \tan a + \cos a) = \frac{1}{\sin a} \), we can start by rewriting \(\tan a\) as \(\frac{\sin a}{\cos a}\). Thus, our left side becomes: \[ \frac{1}{\frac{\sin a}{\cos a}} \left( \sin a \cdot \frac{\sin a}{\cos a} + \cos a \right) = \frac{\cos a}{\sin a} \left( \frac{\sin^2 a}{\cos a} + \cos a \right). \] This simplifies to: \[ \frac{\cos a}{\sin a} \cdot \left( \frac{\sin^2 a + \cos^2 a \cdot \cos a}{\cos a} \right) = \frac{\cos a}{\sin a} \cdot \left( \frac{1}{\cos a} \right) = \frac{1}{\sin a}. \] Now it's proven! Next, regarding the equations given, first, let's solve \((4\theta - 8) \sin 30^{\circ} = \theta^3 - 8\). Since \(\sin 30^{\circ} = \frac{1}{2}\): \[ (4\theta - 8) \cdot \frac{1}{2} = \theta^3 - 8 \implies 2\theta - 4 = \theta^3 - 8. \] Rearranging gives: \[ \theta^3 - 2\theta - 4 = 0. \] Using synthetic division or testing roots can help solve this cubic equation, but let's save that for later exploration. For the quadratic equation \((Q^2 + 2\theta + 4 = 2)\): \[ Q^2 + 2\theta + 2 = 0 \implies Q^2 = -2\theta - 2. \] Notably, \(\tan(240^\circ) = \tan(180^\circ + 60^\circ) = \tan 60^\circ = \sqrt{3}\), but negative since \(240^\circ\) is in the third quadrant, giving \(\tan(240^\circ) = \sqrt{3}\). Now, regarding the general solutions to the equations: 1. For \(2\cos 2\theta = -0.44\), we have \(\cos 2\theta = -0.22\). The angles that solve this can be found using \(\cos 2\theta = x\) where \(x = -0.22\); the general solution will be: \[ 2\theta = \pm \arccos(-0.22) + 2k\pi. \] Thus, \(\theta = \frac{\pm \arccos(-0.22)}{2} + k\pi\). 2. For \(2\cos^2 \theta - \cos Q = 0\): This gives \(\cos^2 \theta = \frac{1}{2}\) which leads to \(\cos \theta = \pm \frac{1}{\sqrt{2}}\). The solutions are: \[ \theta = \frac{\pi}{4} + k\pi \quad \text{and} \quad \theta = \frac{3\pi}{4} + k\pi. \] Put those values in your math toolbox and you'll be navigating trigonometric equations like a pro!

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy